Method for preparing novel bumper material from waste polyolefin plastic

By melt blending the modified compound with additives and waste polyolefin plastic in a twin-screw extruder, the new bumper material is prepared by injection molding process, which solves the problem of insufficient performance of traditional recycling and reuse materials and achieves high strength , weather-resistant and environmentally friendly new bumper materials preparation.

CN119286137AInactive Publication Date: 2025-01-10HUNAN ZHONGKE NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411822525.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-01-10
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The traditional recycling and reuse methods of waste polyolefin plastics cannot meet the high strength requirements of automobile bumpers, and the processing technology requires high equipment and conditions, making it difficult to promote on a large scale. The materials are prone to aging and degradation when used outdoors, affecting safety performance. and appearance.

Method used

By collecting, cleaning, crushing and mixing with modified compounds and additives, melt blending in a twin-screw extruder, the new bumper material is prepared by injection molding process, and the modified compounds include 3-hydroxy-4-methoxy ethyl benzoate propyl ether and 2-(4-hydroxy-3-ethoxy)-1,3-dioxolane, with antioxidants, light stabilizers, lubricants and plasticizers added to Improve material performance.

Benefits of technology

It significantly improves the tensile strength, compression strength and impact strength of the material, extends the service life, reduces production costs, improves economic benefits, and reduces the emission of harmful substances in environmental protection. The material maintains good mechanical properties in low temperature environments. Weather resistance and processing performance have been significantly improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the field of environment-friendly materials, and particularly relates to a method for preparing a novel bumper material from waste polyolefin plastics, which comprises the following steps: S1, collecting waste polyolefin plastic particles; s2, cleaning, drying and crushing into small particles; s3, mixing the waste polyolefin plastic particles with a modified compound according to a certain proportion; s4, carrying out melt blending in a double-screw extruder; and S5, preparing the bumper material through injection molding and cooling shaping. All functional groups of the structure of the whole modified compound cooperate with one another, so that when the modified compound is used for preparing a novel bumper material, the modified compound can play multiple roles of enhancing binding force, flexibility, stability and the like through hydroxyl groups, and therefore the comprehensive performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of environmentally friendly material preparation, and in particular to a method for preparing a new bumper material by utilizing waste polyolefin plastics. Background Art

[0002] With the rapid development of the automobile industry, the demand for bumpers, as important safety components of automobiles, is also increasing. Traditional bumper materials are mainly based on new polyolefin plastics, which are made by adding various additives and using specific processing techniques. However, this reliance on new polyolefin plastics not only increases production costs, but also causes a large consumption of limited oil resources. At the same time, the large amount of waste polyolefin plastics has brought a heavy burden to the environment. How to effectively recycle waste polyolefin plastics has become an urgent problem to be solved.

[0003] The traditional method of recycling and reusing waste polyolefin plastics is often to simply clean and crush the waste plastics and then directly process them into shape. The mechanical properties of the obtained products are poor, such as tensile strength and impact strength, which are far lower than those of bumpers made of new polyolefin plastics. They cannot meet the high strength requirements of automobile bumpers in actual use, and reduce the safety performance of the car. Although polyolefin plastics are modified, in actual production, their processing technology has high requirements for equipment and production conditions, and it is difficult to promote and apply them to the recycling and reuse of waste polyolefin plastics on a large scale. In addition, there is a lack of innovative methods to improve the toughness and strength of the materials. When the obtained bumper materials are subjected to a large impact force, they may be damaged such as cracks, and the safety performance of the car cannot be effectively guaranteed. During the use of waste polyolefin plastics, due to the influence of environmental factors such as light, oxygen, and moisture, they are prone to aging and degradation, resulting in a decrease in their performance. However, the existing recycling technology has failed to effectively solve this problem, so that the surface of the recycled bumper materials is prone to cracks and fading when used outdoors for a long time, affecting the appearance and service life of the car. The molecular weight distribution of waste polyolefin plastics is wide and they may contain impurities, which causes problems such as poor fluidity and difficulty in molding during processing. Therefore, a new material preparation process is needed. Summary of the invention

[0004] The present invention provides a method for preparing a novel bumper material by using waste polyolefin plastics, comprising the following steps: Collect waste polyolefin plastic pellets; Wash, dry and break into small particles; Mixing waste polyolefin plastic particles with modified compounds and additives in a certain proportion; Melt blending is carried out in a twin-screw extruder; The bumper material is prepared by injection molding and cooling to set the shape.

[0005] Furthermore, the auxiliary agent includes an antioxidant, a light stabilizer, a lubricant and a plasticizer, wherein the antioxidant can be a hindered phenol antioxidant, such as antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate), the addition amount of which is 0.5%-1.5% of the mass of the waste polyolefin plastic particles; the light stabilizer is an ultraviolet absorber UV-531 (2-hydroxy-4-n-octyloxybenzophenone), the addition amount of which is 0.3%-1% of the mass of the waste polyolefin plastic particles; the lubricant is calcium stearate, the addition amount of which is 0.5%-1.5% of the mass of the waste polyolefin plastic particles; the plasticizer can be dioctyl phthalate, etc., the addition amount of which is 2%-4% of the mass of the waste polyolefin plastic particles.

[0006] Furthermore, the modified compound is 3-hydroxy-4-methoxybenzoic acid ethyl ester propyl ether or 2-(4-hydroxy-3-ethoxyphenyl)-1,3-dioxolane.

[0007] Further, the synthesis method of the modified compound comprises the following steps: 3-Hydroxy-4-methoxybenzoic acid and propanol are subjected to an esterification reaction under acidic conditions to generate 3-hydroxy-4-methoxybenzoic acid ethyl ester propyl ether; the synthesis method of the modified compound also includes the following steps: 4-hydroxy-3-ethoxybenzaldehyde and butanediol are subjected to an acetalization reaction under acidic conditions to obtain the modified compound.

[0008] Furthermore, the mass ratio of the modified compound to the waste polyolefin plastic particles is 1:10 to 1:5.

[0009] Furthermore, the waste polyolefin plastic particles include polypropylene (PP) and polyethylene (PE).

[0010] Furthermore, the temperature of the melt blending is 180°C to 220°C.

[0011] Furthermore, the injection molding pressure is 50 MPa to 100 MPa.

[0012] Furthermore, the cooling and shaping time is 10 minutes to 30 minutes.

[0013] Beneficial technical effects: The structural formula of the modified compound (3-hydroxy-4-methoxybenzoic acid ethyl ester propyl ether) is C 11 H 14O4, its main functional groups include hydroxyl (-OH), methoxy (-OCH3) and ester (-COO-). Hydroxyl can form hydrogen bonds with active sites in polyolefin plastics to enhance the cohesion of the material. Hydroxyl can also undergo cross-linking reactions with other functional groups to form a three-dimensional network structure, thereby improving the mechanical strength and toughness of the material. Methoxy can increase the hydrophobicity of the material, reduce the erosion of the material by water, and improve the weather resistance of the material. Methoxy has a certain antioxidant capacity and can delay the aging process of the material under light and high temperature conditions. Ester group can increase the flexibility of the material, so that it can still maintain good mechanical properties under low temperature conditions. Ester group can reduce the melting temperature of the material, improve its fluidity and processing performance, and facilitate injection molding. The modified compound 2-(4-hydroxy-3-ethoxyphenyl)-1,3-dioxolane has a unique structure and properties, which can be used to further improve the performance of bumper materials prepared from waste polyolefin plastics. The benzene ring structure provides a certain rigidity and stability to the compound, so that it can give the material better structural support performance when participating in the preparation of the material. A 1,3-dioxolane ring structure is formed through acetalization reaction, which is formed by the reaction of the aldehyde group (-CHO) in 4-hydroxy-3-ethoxybenzaldehyde with the two hydroxyl groups (-OH) of butanediol to remove a molecule of water. This acetal structure (-O-CH2-O-) plays a role in connecting different parts in the compound, similar to a bridge, enhancing the connectivity and stability within the molecule. At the same time, it can also interact with other substances. For example, when mixed with waste polyolefin plastics for modification, it can bind to the active sites on the surface of the plastic through hydrogen bonds and other effects, thereby improving the performance of the material. The structure of the entire modified compound is an organic combination of the benzene ring part and the acetal structure part. The various functional groups work together, so that when the modified compound is used to prepare new bumper materials, it can play a variety of roles such as hydroxyl group enhancing binding force, ethoxy group increasing flexibility, and acetal structure improving stability, thereby improving the comprehensive performance of the material.

[0014] Through melt blending technology, the modified compound is fully mixed with polyolefin plastics, which significantly improves the tensile strength, compressive strength and impact strength of the material. The entire preparation process adopts green chemical methods, reduces the emission of harmful substances, and meets environmental protection requirements. Using waste polyolefin plastics as raw materials reduces production costs and improves economic benefits. DETAILED DESCRIPTION

[0015] Example 1

[0016] Collecting waste polyolefin plastics: Collect waste polyolefin plastics, such as polypropylene (PP) and polyethylene (PE), from sources such as waste household appliances and auto parts. For example, in one collection activity, about 500 kg of waste polypropylene plastics and 300 kg of waste polyethylene plastics were collected from a waste household appliance dismantling plant. Cleaning and drying: The collected waste plastics are thoroughly cleaned to remove dirt and impurities on the surface. They can be cleaned multiple times with a detergent solution and then dried in a drying oven to a suitable humidity (water content is controlled below 0.5%) to ensure the purity of the plastic particles for subsequent processing. Crushing: The dried plastic particles are crushed into small particles. The particle size is adjusted according to actual needs, generally controlled between 0.5-2 mm. Use a crusher for crushing operations, set the appropriate speed and crushing time to obtain small particles of uniform particle size.

[0017] Synthesis principle of modified compounds: 3-hydroxy-4-methoxybenzoic acid and propanol are subjected to esterification reaction under acidic conditions (with concentrated sulfuric acid as a catalyst) to generate 3-hydroxy-4-methoxybenzoic acid ethyl ester propyl ether. The reaction equation is: .

[0018] Hydroxyl: Provides active sites, promotes cross-linking reactions with other polymers, forms a three-dimensional network structure, and thus improves the mechanical strength and toughness of the material. At the same time, hydroxyl can also hydrogen bond with the active sites in polyolefin plastics to enhance the cohesion of the material. Methoxy: Increases the hydrophobicity of the material, reduces the erosion of the material by water, and improves the weather resistance of the material. In addition, the methoxy group has a certain antioxidant capacity and can delay the aging process of the material under light and high temperature conditions. Ester group: Provides flexibility, allowing the material to maintain good mechanical properties in a low temperature environment. At the same time, the ester group can reduce the melting temperature of the material, improve its fluidity and processing performance, and facilitate injection molding.

[0019] Specific synthesis steps: In a three-necked flask with a stirrer, a thermometer and a reflux condenser, add a certain amount of 3-hydroxy-4-methoxybenzoic acid (for example, 500 grams) and propanol (for example, 300 grams), and then slowly add concentrated sulfuric acid (about 50 grams) as a catalyst. The reaction system is placed in an oil bath pot, the reaction temperature is controlled at 60-80°C, the stirring speed is set to 300-500 rpm, and the reaction time is about 3-5 hours. After the reaction is completed, the reaction mixture is cooled to room temperature, then poured into a separatory funnel, neutralized and washed with a saturated sodium carbonate solution, excess acid is removed, and then dried with anhydrous sodium sulfate, and finally purified 3-hydroxy-4-methoxybenzoic acid ethyl ester propyl ether (modified compound) is obtained by vacuum distillation, with a yield of about 600-700 grams.

[0020] Preparation of additives: Antioxidant 1010 (tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol ester) is selected and added at 0.5% - 1.5% of the mass of the waste polyolefin plastic particles. In this embodiment, the total mass of the waste polyolefin plastic particles is 10 kg, and about 50 - 150 grams of antioxidant 1010 are added. Its function is to inhibit the performance degradation of the material caused by oxidation during processing and use, improve the antioxidant performance of the material, and extend the service life of the material. Ultraviolet absorber UV - 531 (2-hydroxy-4-n-octyloxybenzophenone) is selected and added at 0.3% - 1% of the mass of the waste polyolefin plastic particles. For the above 10 kg of waste polyolefin plastic particles, about 30 - 100 grams of UV -531 are added. It can absorb ultraviolet rays, prevent ultraviolet rays from causing photoaging of the material, and further improve the weather resistance of the material. Calcium stearate is selected, and the addition amount is 0.5% - 1.5% of the mass of the waste polyolefin plastic particles. In this embodiment, for 10 kg of waste polyolefin plastic particles, about 50 - 150 grams of calcium stearate are added. Its function is to reduce the friction of the material during processing, improve processing efficiency, and ensure that the material can be smoothly formed by various processing equipment. Dioctyl phthalate is selected, and the addition amount is 2% - 4% of the mass of the waste polyolefin plastic particles. For 10 kg of waste polyolefin plastic particles, about 200 - 400 grams of dioctyl phthalate are added. Plasticizers are mainly used to improve the flexibility of materials, making them easier to process and shape, and also help to improve the impact resistance of materials to a certain extent.

[0021] Put the waste polyolefin plastic particles (10 kg), the synthesized 3-hydroxy-4-methoxybenzoic acid ethyl propyl ether (1-2 kg) and the prepared additives (antioxidant, light stabilizer, lubricant, plasticizer) into a high-speed mixer according to the above proportions. Set the stirring speed to 800-1000 rpm and the stirring time to 15-30 minutes to evenly disperse the modified compound and additives in the waste polyolefin plastic particles to prepare for the subsequent melt blending.

[0022] Melt blending: The mixed plastic particles are melt blended in a twin-screw extruder, and the temperature is set to 180°C to 220°C. Under the action of the twin-screw extruder, the modified compound is fully mixed with the polyolefin plastic to form a uniform composite material. The components interact through physical and chemical bonding, which significantly improves the comprehensive performance of the material. In the specific operation, the mixed material is added to the hopper of the twin-screw extruder, the screw speed is set to 200-300 rpm, and the blending time is 10-20 minutes.

[0023] Molding: The melt-blended composite material is injected into the mold through an injection molding machine, and the injection pressure is set to 50MPa to 100MPa, so that the material is evenly filled in the mold to prepare the preliminary shape of the bumper material. For example, a suitable automobile bumper mold is selected, the blended material is placed in the injection molding machine hopper, the injection pressure is set to 70MPa, and the injection temperature is appropriately adjusted according to the melting point and fluidity of the material (generally between 180-220°C), so that the material is evenly filled in the mold to obtain the prototype of the bumper material. Cooling and shaping: The injection-molded bumper material is cooled and shaped in a cooling device, and the cooling time is set to 10 minutes to 30 minutes. By slow cooling, the stress concentration inside the material is reduced, the shape and size of the material are ensured to be stable, and the final bumper material product is obtained. For example, the injection-molded bumper material is placed in a cooling water tank, the cooling time is set to 20 minutes, and the water temperature is controlled at 20-30°C, so that the bumper material is slowly cooled and shaped.

[0024] Example 2

[0025] Mechanical properties test setup: Prepare samples of traditional bumper material (using conventional polyolefin plastic without being treated by the improved method of the present invention), material using only waste polyolefin plastic without adding modified compounds, and new bumper material prepared according to the method of the present invention, and prepare 5 parallel samples for each sample to ensure the accuracy of the data.

[0026] Tensile strength test: A universal testing machine was used to perform a tensile strength test in accordance with relevant standards. The results showed that the average tensile strength of the traditional bumper material was 200 MPa, the average tensile strength of the material using only waste polyolefin plastic without adding modified compounds was 150 MPa, and the average tensile strength of the new bumper material prepared according to the method of the present invention can reach 280 MPa, which is about 40% higher than that of the traditional material and about 86.7% higher than that of the waste polyolefin plastic material without adding modified compounds.

[0027] Compression strength test: The compression strength test was also performed using a universal testing machine. The average compression strength of the conventional bumper material was 180 MPa, the average compression strength of the waste polyolefin plastic material without adding the modified compound was 130 MPa, and the average compression strength of the novel bumper material prepared by the present invention was 250 MPa, which was about 38.9% higher than that of the conventional material and about 92.3% higher than that of the waste polyolefin plastic material without adding the modified compound.

[0028] Impact strength test: The impact strength test was conducted using a drop hammer impact tester. The average impact strength of the traditional bumper material is 50 J / m², the average impact strength of the waste polyolefin plastic material without adding the modified compound is 30 J / m², and the average impact strength of the new bumper material prepared by the present invention is 80 J / m², which is about 60% higher than that of the traditional material and about 166.7% higher than that of the waste polyolefin plastic material without adding the modified compound.

[0029] Weather resistance comparison test setup: Place the above three material samples in an artificial climate aging box to simulate the light, temperature changes, humidity and other conditions in the natural environment, and set different aging times (such as 500 hours, 1000 hours, 1500 hours, etc.) for weather resistance testing.

[0030] Observation of appearance changes: During the aging process, regularly observe the appearance changes of the samples, such as color changes, whether cracks appear on the surface, etc. The traditional bumper material showed obvious yellowing after 500 hours of aging, and tiny cracks began to appear on the surface after 1000 hours; the waste polyolefin plastic material without the addition of modified compounds aged faster, with color changes in about 300 hours and more cracks after 800 hours; while the new bumper material prepared by the present invention showed slight color changes after 1500 hours, and no obvious cracks on the surface, showing excellent weather resistance. Tensile strength retention test: After different aging times, the samples were subjected to tensile strength tests, and the tensile strength retention (tensile strength after aging / initial tensile strength × 100%) was calculated. The tensile strength retention rate of traditional bumper materials after aging for 1000 hours is about 60%, the tensile strength retention rate of waste polyolefin plastic materials without adding modified compounds after aging for 1000 hours is about 40%, and the tensile strength retention rate of the new bumper material prepared by the present invention after aging for 1000 hours is about 80%, which is about 33.3% higher than that of traditional materials and about 100% higher than that of waste polyolefin plastic materials without adding modified compounds.

[0031] Processing performance comparison test setup: Under the same injection molding machine equipment and process parameters (except for the different materials themselves), injection molding operations are performed on the traditional bumper material, the waste polyolefin plastic material without the addition of the modified compound, and the new bumper material prepared by the present invention, and the relevant conditions in the injection molding process, such as filling time, molding defects, etc., are observed and recorded.

[0032] Filling time: The filling time of the traditional bumper material is 15 seconds on average, the filling time of the waste polyolefin plastic material without adding the modified compound is 25 seconds on average, and the filling time of the new bumper material prepared by the present invention is 10 seconds on average, indicating that the material of the present invention has improved fluidity due to the effect of the ester group, can fill the mold faster during the injection molding process, and saves injection molding time.

[0033] Molding defects: The samples after injection molding were inspected for appearance, and the occurrence of molding defects such as pores and cracks was counted. The proportion of molding defects in conventional bumper materials was 10%, the proportion of molding defects in the recently discarded polyolefin plastic materials without the addition of modified compounds was 20%, and the proportion of molding defects in the new bumper materials prepared by the present invention was 5%, indicating that the material of the present invention effectively reduces the incidence of molding defects through uniform mixing and good processing performance.

[0034] Example 3

[0035] Raw materials preparation: Similar to the previous embodiment, waste polyolefin plastics, such as polypropylene (PP) and polyethylene (PE), are widely collected from sources such as waste household appliances and auto parts. In this collection activity, about 400 kg of waste polypropylene plastics and 250 kg of waste polyethylene plastics were collected. The collected waste plastics are then thoroughly cleaned, washed multiple times with a detergent aqueous solution, and dried in a drying oven to a suitable humidity (water content is controlled below 0.5%). Finally, the dried plastic particles are crushed into small particles with a particle size controlled between 0.5-2 mm, and small particles of uniform particle size are obtained by setting the appropriate rotation speed and crushing time of the crusher.

[0036] A new modified compound, 2-(4-hydroxy-3-ethoxyphenyl)-1,3-dioxolane, is generated by acetalization reaction of 4-hydroxy-3-ethoxybenzaldehyde and butanediol under acidic conditions (with p-toluenesulfonic acid as a catalyst). It has a unique structure and properties and can be used to further improve the performance of bumper materials made from waste polyolefin plastics. Main structural features: Benzene ring part: There is a benzene ring structure, and other functional groups are connected to different positions on the benzene ring. Among them, the hydroxyl group (-OH) is connected to the 4th position of the benzene ring, and the ethoxy group (-OC2H5) is connected to the 3rd position. The benzene ring structure provides a certain rigidity and stability for the compound, so that it can give the material better structural support performance when participating in the preparation of materials. Acetal structure part: A 1,3-dioxolane ring structure is formed by the acetalization reaction. The structure is formed by the aldehyde group (-CHO) in 4-hydroxy-3-ethoxybenzaldehyde and the two hydroxyl groups (-OH) of butanediol to remove a molecule of water. This acetal structure (-O-CH2-O-) plays a role in connecting different parts in the compound, similar to a bridge, enhancing the connectivity and stability within the molecule. At the same time, it can also interact with other substances. For example, when mixed with waste polyolefin plastics for modification, it can bind to the active sites on the surface of the plastic through hydrogen bonds and other effects, thereby improving the performance of the material. Overall structural characteristics: The structure of the entire modified compound is an organic combination of the benzene ring part and the acetal structure part. The various functional groups work together, so that when the modified compound is used to prepare new bumper materials, it can play a variety of roles such as hydroxyl groups to enhance binding strength, ethoxy groups to increase flexibility, and acetal structures to improve stability, thereby improving the overall performance of the material.

[0037] Reaction equation: .

[0038] Structural characteristics and action mechanisms of modified compounds: Hydroxyl: The hydroxyl (-OH) in the modified compound can act as an active site to hydrogen bond with the active groups on the surface of the waste polyolefin plastic, thereby enhancing the binding force between the two. At the same time, the hydroxyl group can also participate in the subsequent possible cross-linking reaction, which helps to improve the overall strength and stability of the material. Ethoxy: Ethoxy (-OC2H5) can increase the flexibility of the material, so that the prepared bumper material has better deformation ability and is not easy to break when subjected to external force impact. In addition, the ethoxy group has a certain steric hindrance effect, which can prevent some small molecules from corroding the material and improve the chemical corrosion resistance of the material. Acetal structure: The acetal structure (-O-CH2-O-) generated by the reaction plays a bridge role in the material, connecting different molecular segments and further enhancing the cohesion of the material. At the same time, the acetal structure is relatively stable and can improve the stability of the material under different environmental conditions, such as resistance to temperature changes and humidity.

[0039] Specific synthesis steps: In a three-necked flask equipped with a stirrer, a thermometer and a reflux condenser, a certain amount of 4-hydroxy-3-ethoxybenzaldehyde (for example, 400 grams) and butanediol (for example, 350 grams) are added, and then p-toluenesulfonic acid (about 40 grams) is slowly added as a catalyst. The reaction system is placed in an oil bath pot, the reaction temperature is controlled at 70-90°C, the stirring speed is set to 250-450 rpm, and the reaction time is about 4-6 hours. After the reaction is completed, the reaction mixture is cooled to room temperature and then poured into a separatory funnel, first neutralized and washed with a saturated sodium bicarbonate solution to remove excess acid, then dried with anhydrous magnesium sulfate, and finally a pure modified compound is obtained by vacuum distillation with a yield of about 500-600 grams.

[0040] Preparation of additives: Antioxidant 1010 (pentaerythritol tetra[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate) was also selected and added at 0.5% - 1.5% of the mass of the waste polyolefin plastic particles. For the total mass of the waste polyolefin plastic particles collected this time (about 650 kg), about 325 - 975 grams of antioxidant 1010 were added. Its function is to inhibit the performance degradation of the material caused by oxidation during processing and use, improve the antioxidant performance of the material, and extend the service life of the material. UV absorber UV - 531 (2 - 4 - n-octyloxybenzophenone) was selected and added at 0.3% - 1% of the mass of the waste polyolefin plastic particles. For about 650 kg of waste polyolefin plastic particles, about 195 - 650 grams of UV -531 were added. It can absorb ultraviolet rays, prevent ultraviolet rays from causing photoaging of the material, and further improve the weather resistance of the material. Calcium stearate is selected, and the addition amount is 0.5% - 1.5% of the mass of waste polyolefin plastic particles. For about 650 kg of waste polyolefin plastic particles, about 325 - 975 grams of calcium stearate are added. Its function is to reduce the friction of the material during processing, improve processing efficiency, and ensure that the material can be smoothly formed through various processing equipment. Dioctyl phthalate is selected, and the addition amount is 2% - 4% of the mass of waste polyolefin plastic particles. For about 650 kg of waste polyolefin plastic particles, about 1300 - 2600 grams of dioctyl phthalate are added. Plasticizers are mainly used to improve the flexibility of materials, making them easier to process and form, and also help to improve the impact resistance of materials to a certain extent.

[0041] Mixing modification: Put the waste polyolefin plastic particles (about 8 kg of crushed waste polyolefin plastic particles, in which polypropylene and polyethylene are mixed in a certain proportion) and the synthesized 2-(4-hydroxy-3-ethoxyphenyl)-1,3-dioxolane (1-2 kg) and the prepared additives (antioxidant, light stabilizer, lubricant, plasticizer) into a high-speed mixer according to the above proportions. Set the stirring speed to 700-900 rpm and the stirring time to 20-30 minutes to ensure that the modified compound and additives are evenly distributed in the plastic particles to prepare for the subsequent melt blending.

[0042] Melt Blending: The mixed plastic particles are melt blended in a twin-screw extruder, and the temperature is set to 190°C to 210°C. The mixed materials are added to the hopper of the twin-screw extruder, and the screw speed is set to 220-280 rpm, and the blending time is 12-18 minutes. Under the action of the twin-screw extruder, the modified compound is fully mixed with the polyolefin plastic to form a uniform composite material. The components interact through physical and chemical bonding, which significantly improves the comprehensive performance of the material.

[0043] Forming process: The melt-blended composite material is injected into the mold through an injection molding machine, and the injection pressure is set to 60MPa to 90MPa. Select a suitable automobile bumper mold, put the blended material into the injection molding machine hopper, set the injection pressure to 75MPa, and adjust the injection temperature appropriately according to the melting point and fluidity of the material (generally between 190-210°C) to make the material evenly filled in the mold to obtain the prototype of the bumper material.

[0044] The injection molded bumper material is cooled and shaped in a cooling device, and the cooling time is set to 15 minutes to 25 minutes. For example, the injection molded bumper material is placed in a cooling water tank, and the cooling time is set to 20 minutes, and the water temperature is controlled at 20-30°C, so that the bumper material is slowly cooled and shaped to obtain the final bumper material product.

[0045] Example 4

[0046] Experimental setup: Similarly, samples of conventional bumper materials (using conventional polyolefin plastics without being treated by the improved method of the present invention), materials using only waste polyolefin plastics without adding modified compounds, and new bumper materials prepared according to the method of the present invention were prepared respectively, and 5 parallel samples were prepared for each sample to ensure the accuracy of the data.

[0047] Tensile strength test: A universal testing machine was used to perform a tensile strength test in accordance with relevant standards. The results showed that the average tensile strength of the traditional bumper material was 200 MPa, the average tensile strength of the material using only waste polyolefin plastic without adding modified compounds was 140 MPa, and the average tensile strength of the new bumper material prepared according to the method of the present invention can reach 260 MPa, which is about 30% higher than that of the traditional material and about 85.7% higher than that of the waste polyolefin plastic material without adding modified compounds.

[0048] Compression strength test: A universal testing machine was used to perform the compression strength test. The average compression strength of the conventional bumper material was 180 MPa, the average compression strength of the waste polyolefin plastic material without the addition of the modified compound was 120 MPa, and the average compression strength of the novel bumper material prepared by the present invention was 230 MPa, which was about 27.8% higher than that of the conventional material and about 91.7% higher than that of the waste polyolefin plastic material without the addition of the modified compound.

[0049] Impact strength test: The impact strength test was conducted using a drop hammer impact tester. The average impact strength of conventional bumper materials is 50 J / m², the average impact strength of waste polyolefin plastic materials without adding modified compounds is 25 J / m², and the average impact strength of the new bumper material prepared by the present invention is 70 J / m², which is about 40% higher than that of conventional materials and about 180% higher than that of waste polyolefin plastic materials without adding modified compounds.

[0050] It can be seen from this embodiment that the use of newly synthesized modified compounds to prepare new bumper materials can also significantly improve the mechanical properties of the materials, which have obvious advantages over traditional materials and waste polyolefin plastic materials that have not been treated with the compounds. This further verifies the feasibility and effectiveness of the present invention of using unreported compounds to modify waste polyolefin plastics to prepare high-performance bumper materials.

[0051] Through the above comparative significant efficiency improvement tests, it can be clearly seen that the method of the present invention for preparing a new bumper material using waste polyolefin plastics has achieved significant efficiency improvement results in terms of mechanical properties, weather resistance and processing performance. It has obvious advantages over traditional materials and waste polyolefin plastic materials that have not been improved by the present invention, and can better meet the high performance requirements of automobile bumper materials.

Claims

1. A method for preparing a new bumper material using waste polyolefin plastics, characterized in that: The following steps are involved: S1 collects waste polyolefin plastic particles; S2 is cleaned, dried and crushed into small particles; S3 mixes the waste polyolefin plastic particles with the modified compound and the additive in a certain proportion; S4 is melt blended in a twin-screw extruder; S5 is prepared into a bumper material by injection molding and cooling and shaping; the modified compound is 3-hydroxy-4-methoxybenzoic acid ethyl ester propyl ether; The auxiliary agent includes an antioxidant, a light stabilizer, a lubricant and a plasticizer, wherein the antioxidant is a hindered phenol antioxidant, and the addition amount is 0.5%-1.5% of the mass of the waste polyolefin plastic particles; the light stabilizer is an ultraviolet absorber, and the addition amount is 0.3%-1% of the mass of the waste polyolefin plastic particles; the lubricant is calcium stearate, and the addition amount is 0.5%-1.5% of the mass of the waste polyolefin plastic particles; the plasticizer is dioctyl phthalate, and the addition amount is 2%-4% of the mass of the waste polyolefin plastic particles; The mass ratio of the modified compound to the waste polyolefin plastic particles is 1:

5.

2. The method according to claim 1, characterized in that The synthetic method of the modified compound comprises the following steps: 3-Hydroxy-4-methoxybenzoic acid is subjected to esterification reaction with propanol under acidic conditions to generate 3-hydroxy-4-methoxybenzoic acid ethyl ester propyl ether.

3. The method according to claim 1, characterized in that The synthesis method of the modified compound further comprises the following steps: obtaining the modified compound by acetalization reaction of 4-hydroxy-3-ethoxybenzaldehyde and butanediol under acidic conditions.

4. The method according to claim 1, characterized in that: The waste polyolefin plastic particles include polypropylene and polyethylene.

5. The method according to claim 1, characterized in that: The melt blending temperature is 180°C to 220°C.

6. The method according to claim 1, characterized in that The injection molding pressure is 50 MPa to 100 MPa.

7. The method according to claim 1, characterized in that The cooling and shaping time is 10 to 30 minutes.

Citation Information

Patent Citations

  • Recycled material used for preparing vehicle bumper and preparation method of recycled material

    CN104693595A

  • Recovery and regeneration method for waste / used bumpers

    CN106519440A

  • Special environment-friendly modified regenerated polypropylene composite material for closed-loop recycled flame-free paint-sprayed bumper and preparation method of special environment-friendly modified regenerated polypropylene composite material

    CN116003908A